2010
DOI: 10.1111/j.1745-493x.2010.03197.x
|View full text |Cite
|
Sign up to set email alerts
|

Job Types in the Supply Chain Management Profession

Abstract: There is little academic consensus on a definition of supply chain management (SCM). Education and research could benefit from a better understanding of how practice is defining the profession, in terms of the type of jobs associated with SCM. Existing definitions of SCM suggest two archetypal job functions: functional integrator and process manager. To compare existing definitions to practice, we analyzed job descriptions associated with the field of SCM using computerized text analysis. We find tentative sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 51 publications
3
36
0
2
Order By: Relevance
“…The study found that internal collaboration needs to be comprehensive across all departments, rather than just those involved in purchasing and sustainability through a distinct employer involvement that includes a mutual understanding of the definition and vision in terms of understanding the distinct approach to sustainability and SSCM. In terms of external enablers, external collaboration, and the supplier relationship are core categories for a successful supply chain policy implementation, which is in alignment with previous research [35]. However, the article extends previous research by defining the modes of internal and external collaboration that enable a successful sustainable policy implementation in textile supply chains.…”
supporting
confidence: 67%
See 1 more Smart Citation
“…The study found that internal collaboration needs to be comprehensive across all departments, rather than just those involved in purchasing and sustainability through a distinct employer involvement that includes a mutual understanding of the definition and vision in terms of understanding the distinct approach to sustainability and SSCM. In terms of external enablers, external collaboration, and the supplier relationship are core categories for a successful supply chain policy implementation, which is in alignment with previous research [35]. However, the article extends previous research by defining the modes of internal and external collaboration that enable a successful sustainable policy implementation in textile supply chains.…”
supporting
confidence: 67%
“…Moreover, a lack of corporate structures and processes also constitutes an internal barrier for SSCM [11]. With regard to function-related issues, a lack of necessary management skills [17] adequate training, knowledge [34] or incentives [35] constitute internal barriers.…”
Section: Internal Barriersmentioning
confidence: 99%
“…The authors briefly describe five archetypes with three balanced integration archetypes and two customer-leaning integration archetypes in different nuances. LSCM job type archetypes were deviated from collected job descriptions from a major employment website to provide suggestions on how training and professional development should occur [48]. Text analysis was used to mechanically code the job descriptions and hierarchical cluster analysis using Ward's method was applied to identify eight archetypes.…”
Section: Discussionmentioning
confidence: 99%
“…Further, they indicated how MBA-level SCM programmes of the top business schools in the US respond to that employers' needs. Rossetti and Dooley (2010) analysed job ads associated with the field of SCM and pointed out three major types of SCM jobs, namely sourcing manager, operations consultant and supply chain information manager. Cacciolatti and Molinero (2013) collected SCM job ads in the UK and after a detailed analysis concluded that all SCM jobs could be grouped into two main categories "managers" and "clerks".…”
Section: Literature Reviewmentioning
confidence: 99%